Simple synthesis of 32P-labelled inositol hexakisphosphates for study of phosphate transformations - Whitfield, Hayley (Plant and soil, 2018)
BACKGROUND AND AIMS: In many soils inositol hexakisphosphate in its various forms is as abundant as inorganic phosphate. The organismal and geochemical processes that exchange phosphate between inositol hexakisphosphate and other pools of soil phosphate are poorly defined, as are the organisms and enzymes involved. We rationalized that simple enzymic synthesis of inositol hexakisphosphate labeled with 32P would greatly enable study of transformation of soil inositol phosphates when combined with robust HPLC separations of different inositol phosphates